Rural Green Tourism: Current Trends and Development Prospects - Haba, Myroslava (Information & Media, 2020)
The article determines that in the current conditions of development of the economy of Ukraine the structure of the tourism industry is changing due to the development of perspective types of tourism, including rural green tourism. The purpose of the article is to identify the features, trends and prospects of rural green tourism development. Results. One of the newest forms of tourism is rural green tourism - a priority area in the tourism industry, which opens opportunities for solving a number of problems of rural development. Rural green tourism is a specific form of recreation in the countryside, which has ample opportunity to use the natural, material and cultural potential of certain regions. In the structure of the tourist complex of Ukraine of recent years rural green tourism has become one of the leading and most attractive types of tourism specialization, which requires increase its effective development and management. The analysis of the activity of rural green tourism objects will make it possible to increase the attractiveness of rural green tourism. The development of rural green tourism in the regions of Ukraine every year becomes more powerful and one of the perspective ways of solving social issues regarding employment in all regions and their socio - economic development. The directions of rural green tourism development affect its development prospects. Value/originality. Rural green tourism is viewed from two sides: first, as a promising and attractive destination in the tourism industry, and second, as an object that will increase the potential and potential of rural areas. In the course of the study, the motivational content of rural green tourism was identified as an opportunity to extend the tourist appeal of specialized tourism. For the developing of green tourism in Ukraine promotes the study of international experience of tourism.